The Level of Productivity in Traded and Non-Traded Sectors for a Large Panel of Countries - Mano, Rui (IMF Working Papers; Working Paper ;, 2015)
This paper explains in detail the construction of series for productivity in the traded and nontraded sectors for a panel of 56 countries spanning 1989-2012. The level of productivity in each sector is defined as real value added per worker in constant 2005 Purchasing Power Parity (PPP) U.S. dollars. To construct these series, we collect industry-level data from several sources, and classify individual industries as traded/non-traded using their ratio of exports to value added. Finally, we aggregate the industry data up to a traded sector and a non-traded sector, accordingly. This new dataset has two main advantages relative to existing datasets: (i) it defines more finely the traded/non-traded sectors, by drawing on much more disaggregated industry source data; and (ii) it allows for meaningful comparisons of the level of productivity across countries/sectors because sectoral productivity is adjusted by its own price level.